RuBricks Pilipinas Inc. feasibility study on a large-scale manufacturing system of converting trash to bricks - Dela Cruz, Nathaniel Angelo G.; Dizon, Orel Jon F.; Domingo, Angelo Z.; Luces, Johnlee B.
This study shows the quantitative analysis of the feasibility of converting bricks from residual wastes. A technical analysis was conducted through tests conducted by the Bureau of Testing and Standards of the DPWH. The tests proved that RuBRICKS (Re-Used BRICKS) can withstand a load of 44.2 tons equivalent to a 16-wheeler truck. Thus, it is suggested that this product be initially used for pavements. After having the knowledge of the usage of this product, the demand for bricks was defined. As computed after data gathering and interviews, DPWH together with the Quezon City government is willing to use RuBRICKS for the pavement of sidewalks of National and local road in Quezon City amounting to more than 29 Million bricks. This amount is expected to be consumed within three years, in relation to a local government's term. Having the knowledge on the demand to be produced, the necessary amount of input was also determined amounting to 2.14 Billion cubic meters of residual wastes. Inputs are defined as solid wastes that cannot be composted or recycled and are currently accumulating on dumpsites. The Metro Manila Development Authority records a total of 9.3 Billion cubic meters which is much higher than the necessary input, as computed. With an abundant source of residual wastes, a supply deficit is unlikely to occur. RuBRlCKS has the quality compliance to its technical requirements and has high market feasibility. In conclusion this product is commercially viable and has potential for growth and sustainability for succeeding years.